Decision system analysis of advertising agency decisions. - Singh, Bajaj Gurmit. (2008)
A study of how advertising decisions are made by marketing agencies via the use of DSA - Decision Systems Analysis. DSA applies the concept of flowcharts development to document the decision making processes.